Seismic performance of bridge pier integrated by multiple steel pipes with directly-connected piles using soil-water coupled three-dimensional elasto-plastic finite element analysis - Muhammad Mahmood Ul Hassan; Koichi Isobe; Yasumasa Soga; Yasuo Sawamura; Hiroki Sugiyama; Masatsugu Shinohara (Soils and Foundations)
A bridge pier integrated by multiple steel pipes with directly-connected piles was proposed as a way to design a rational foundation for bridge pier structures, and its feasibility was examined by comparing its seismic behaviour with that of a bridge pier with a conventional footing. Through large-scale shaking table tests, employing bridge pier and foundation models at a scale of 1:20, it was verified that the seismic performance of such a bridge pier is comparable to, if not better than, that of a bridge pier with a conventional footing. However, as the shaking table tests utilized only a 2-Hz sine wave as the input, the impact of the relationship between the structure’s natural frequency and the input frequency on the seismic performance, and the response of the structure to irregular ground motion, need further investigation. Therefore, the aim of the present paper is to conduct a reproduction analysis of the results of the above experiment using the soil–water coupled three-dimensional elasto-plastic dynamic finite element analysis method. The analysis will employ a different seismic motion input from that used in the above tests. Through this analytical approach, the paper will elucidate the characteristics related to employing a bridge pier comprised of multiple steel pipes with directly-connected piles.